Pneumatologia do (neo)pentecostalismo brasileiro : convergências, divergências e a proposta de um pós-pentecostalismo - Maciel, Moisés Brasil (2023)
The present research (neo) Pentecostal Pneumatology: convergences, divergences and the proposal of a post-Pentecostalism, aims to present the Pentecostal pneumatology of the Assemblies of God and neo-Pentecostal of the Universal Church of the Kingdom of God (IURD). The research moves in response to the question of what convergences and divergences these two Protestant segments have regarding their pneumatologies. To this end, the bibliographic method will be used, starting, firstly, with a historical presentation of movements that directly and indirectly influenced the emergence of these two denominations, followed by their respective pneumatologies. It then contrasts the statements of the Assemblies of God and the Universal Church of the Kingdom of God on the doctrine of the Holy Spirit. Finally, it opens a discussion about the possibility of a new moment resulting from Pentecostalism, called Post-Pentecostalism.